PROBLEMS OF STRATEGIC PLANNING OF OIL AND GAS INDUSTRY IN A TURBULENT ENVIRONMENT - Amer, A.B.; Meshkov, V.R. (Scientific Journal of Pedagogy and Economics, 2020)
In market conditions the external environment, economy, technology, politics, culture and society in general that affect the organization's activities are constantly changing. Therefore, strategic analysis and planning is a tool for forming an attitude to the future of the organization taking into account these changes, as a tool for reacting and adapting to such changes. To ensure the adaptability of strategic planning, effective contingency measures must be provided for in all types of planning. At the same time, at each stage of strategic planning, its adaptive potential must be realized. In a competitive economy, most domestic enterprises are required to make qualitatively new decisions for long-term effective development. Planning should facilitate the adaptation of the enterprise to market requirements in accordance with the goals and objectives of the enterprise, its internal capabilities and environmental conditions. In this regard, planning is becoming more and more strategic. However, traditional long-term planning does not lose its relevance, since strategic planning is based on traditional long-term planning. In developed market economies, tools for developing long-term development scenarios for companies have been the subject of research for decades. The experience of foreign forecasting is widely used by Kazakhstani companies today. However, as practice shows, direct use and copying of foreign experience in the development of strategies often lead to errors and distortions. In practice, Kazakh companies need to apply appropriate tools and mechanisms for strategic planning, coordinated and adapted to the specific risks. The goals and main provisions of strategic planning of oil companies are discussed in the article. The role of the oil industry in the main macroeconomic indicators of the country's development is shown.